Kemiskinan dalam bayang-bayang kekayaan alam: Analisis ketimpangan di provinsi Papua Barat - binti mukhlis, auliya zuhrin (Maliki Interdisciplinary Journal, 2025)
West Papua is one of the regions in Indonesia that is known to have abundant natural resources, ranging from mining products, forests, to marine resources. Ironically, despite being blessed with great natural potential, West Papua is actually one of the provinces with the highest poverty rate in Indonesia. This situation raises an awkward question: why poverty remains high amidst the abundance of natural resources. This study aims to analyze welfare inequality in West Papua through a spatial approach, and relate it to the achievement of the Sustainable Development Goals (SDGs), particularly goal 1 (No Poverty) and goal 10 (Reducing Inequality). Using secondary data from the Central Bureau of Statistics (BPS) for 2024 and Geographic Information System (GIS) mapping technology, this study maps the distribution of poverty lines in the Papua Barat region and categorizes them as low, medium, and high.The results of the analysis show that there are significant inequalities between districts/cities in Papua Barat. Some regions such as Teluk Bintuni and Manokwari have high poverty rates, while regions such as Teluk Wondama, South Manokwari, and Arfak Mountains show lower poverty rates. This finding confirms the existence of spatial disparities and development quality between regions. This research contributes to the development of evidence-based policy, particularly in equitable and sustainable regional development planning. Spatial visualization through thematic maps is expected to be a strategic tool in tackling poverty that is not only economic, but also structural and multidimensional as indicated in the structural poverty theory. With this approach, it is hoped that West Papua's development can be more inclusive and in accordance with the principles of social justice and sustainability promoted in the SDGs.